A review of factors affecting SCC initiation and propagation in pipeline carbon steels - Abubakar, Shamsuddeen Ashurah; Mori, Stefano; Sumner, Joy (MDPI, 2022)
Pipelines have been installed and operated around the globe to transport oil and gas for decades. They are considered to be an effective, economic and safe means of transportation. The major concern in their operation is corrosion. Among the different forms of corrosion, stress corrosion cracking (SCC), which is caused by stresses induced by internal fluid flow or other external forces during the pipeline’s operation, in combined action with the presence of a corrosive medium, can lead to pipeline failure. In this paper, an extensive review of different factors affecting SCC of pipeline steels in various environmental conditions is carried out to understand their impact. Several factors such as temperature, presence of oxidizers (O2, CO2, H2S, etc.), composition and concentration of medium, pH, applied stress, and microstructure of the metal/alloy have been established to affect the SCC of pipeline steels. SCC susceptibility of a steel at a particular temperature strongly depends on the type and composition of the corrosive medium and microstructure. It was observed that pipeline steels with water quenched and quenched and tempered heat treatments, such as those that consist of acicular ferrite or bainitic ferrite grains, are more susceptible to SCC irrespective of solution type and composition. Applied stress, stress concentration and fluctuating stress facilitates SCC initiation and propagation. In general, the mechanisms for crack initiation and propagation in near-neutral solutions are anodic dissolution and hydrogen embrittlement.
Keywords: stress corrosion cracking; pipeline steels; applied stress; microstructure; anodic dissolution; hydrogen embrittlement